Dielectric properties and negative permittivity performance modulated by dual fillers in CNTs/TiN/CaCu3Ti4O12 ternary composites. Issue 19 (1st October 2022) - Fan, Guohua; Feng, Ting; Qu, Yunpeng; Hao, Chuncheng; Liu, Yao
Abstract: Ceramic composites with negative permittivity have attracted widespread attention during the development of novel electromagnetic metamaterials. Herein, carbon nanotubes/TiN/CaCu3 Ti4 O12 (CNTs/TiN/CaCu3 Ti4 O12 ) ternary composites were prepared, and the effects of dual fillers on the dielectric properties of the ternary composites are discussed. The electrical conductivity increased markedly, and the conduction mechanism changed owing to the percolation of the dual conductor fillers. The switching of the reactance, from negative to positive, suggests that the ternary composites underwent a capacitive-inductive transition. The dielectric permittivity was negative owing to the plasmonic state of the free electrons in the percolating conductor fillers. Regulating the electron concentration by changing the filler content or adjusting the microstructure by changing the relative content of the dual fillers proved to be an effective way to tailor the negative permittivity performance of ternary composites. In addition, conduction loss dominated the dielectric loss mechanism of the negative permittivity composites. The realization and regulation mechanism of the negative permittivity of ternary composites are clarified, shedding light on the preparation and development of negative permittivity materials for various electromagnetic applications.